Isang modyul na lumilinang sa pag-iisip para sa ikaapat na baitang - Tumbaga, Aurelia O. 1948- (1977)
The purpose of the study was to show the ways through which the higher-level thinking skills, the skills requisite to the development of an inquiring mind, can be developed in a module. The concept used is from the discipline of geography. In conclusion, the study assumed that the higher-level thinking skills can be developed in a self-instructional module, provided that the objectives and learning experiences are made for this purpose. In this endeavor, the teacher needs a redirection of orientation. Instead of emphasizing on the accumulation of facts, the major aim should be the development of thinking skills. Creativity is a must in preparing a module.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Geography -- Study and teaching (Elementary) -- Philippines; Social sciences -- Study and teaching (Elementary) -- Philippines; Critical thinking in children -- Philippines; Teaching -- Philippines -- Aids and devices